Phase II study of fluorouracil, leucovorin and interferon alpha-2a in patients with advanced colon cancer - Štabuc, Borut (Radiology and oncology (Ljubljana), 1998)
Based on in viro studies that have demonstrated synergy between fluorouracil (5-FU) and leucovorin (LV) as well as between 5-FU and recombinant alpha-2a interferon (IFN) against colon cancer cell lines a phase II study was carried out to evaluate the toxicity and clinical activity of 5-FU modulated with LV and IFN in patients with metastatic colon cancer. Twenty-two chemotherapy naive patients with measurable metastases of colon cancer have been treated with daily doses of 5-FU 600 mg/m2 in 6-hr intravenous infusion, and of LV 20 mg/m2 intravenously and IFN 6 MU subcutaneously, for 5 days every 4 weeks. Median age was 60 years, median PS (ECOG) was 1 (range 0-2). Liver, soft tissue and lung metastases were found in 12, 5 and 8 patients, respectively. Nineteen patients had a single metastatic site, two double, whereas one had more than two metastatic sites. Patients had 2-9 (mean 5) cycles of treatment.Objective response was observed in 7 patients (32%), and stable disease in 7 patients (32%). Overall median survival was 12.5 months, and for responders 14.4 months. Responses were generally short and median time for progression was 5.5 months. The most frequent adverse reactions were flu-like syndrome (50%), nausea/vomiting (36%), diarhoea (13Č), stomatitis (27%) and leucopenia (13%). This regimen of 5-FU with LV and IFN administration does notappear to be superior to previously published shedules of 5-FU with IFN or 5-FU with LV.
Keywords: Clinical trials, phase ii; Colonic neoplasms; črevesje; debelo črevo; Drug therapy; Drug therapy, combination; Fluorouracil; Interferon alfa-2a; Leucovorin; rak (medicina); Survival analysis; Therapeutic use; zdravljenje